ECONOMIC AND SOCIAL PARTICIPATION OF WOMEN IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Turdiyeva Shokhista (International Scientific and Current Research Conferences, 2023)
To highlight the essence of the Sustainable Development Goals, economic growth, social integration and environmental balance in sustainable development, and measures to increase women's economic and social participation in achieving the Sustainable Development Goals. That is based on the gathering of ideas and the need for action to be taken.